Sorption of selected heavy metal ions from aqueous solutions by mango seed shell derived sorbents - Moyo, Malvin (My University, 2017)
The use of biosorption to complement conventional water treatment techniques has gained widespread appeal partly due to the abundance of waste materials that can be used as low cost biosorbents. However, some materials have not yet been exploited in this regard. This research was aimed at evaluating the biosorption potential of Mangifera indica (mango) seed shells that are readily available in several farming areas of the Limpopo and Mpumalanga Provinces of South Africa. In this work, powdered ethylenediaminetetraacetic acid (EDTA) functionalized biosorbent was prepared from alkali treated biomass of waste mango seed shells. The influence of alkali treatment and EDTA functionalization on the physicochemical properties of the biomass was characterized using Fourier transform infra-red spectroscopy, X-ray diffraction and thermogravimetric analysis. Results confirmed removal of hemicelluloses, conversion of crystalline to amorphous cellulose and the introduction of carboxyl, ester and tertiary amine groups from EDTA. Furthermore, the powdered biosorbent was immobilized using calcium alginate for adaptation to column sorption. The powdered biosorbents were tested for sorption of lead(II) ions using batch sorption experiment. Through EDTA functionalization, improvement in sorption capacity for lead(II) ions from 59.25 mg.g-1 to 306.33 mg.g-1 was realized. The Langmuir and Pseudo-nth order models most suitably simulated the equilibrium and kinetics of sorption by both functionalized and non-functionalized biomaterials. The calcium alginate immobilized biosorbent was evaluated for non-specific sorption of ionic species of copper, chromium, nickel and iron from electroplating wastewater through discontinuous column sorption experiments. Highest copper, chromium, nickel and iron removal was 12.3%, 14.8%, 4.4% and 13.8% from nonacidified samples at an initial pH of 3.4, and 15.5%, 18.7%, 13.7% and 17.3% from samples acidified to an initial pH of 1.8. Repeated sorption-desorption cycles involving acidified wastewater resulted in successive improvement in metal uptake against declining recovery indicating irreversible binding on –COOH groups formed from –CH2OH groups through a redox reaction involving reduction of chromium(VI) to chromium(III).
M. Tech. (Department of Chemistry, Faculty of Applied and Computer Sciences), Vaal University of Technology.
Keywords: Mangifera indica; Biosorption; Alkali treatment; Carboxyl functionalization; Calcium aliginate; Water -- Purification.; Heavy metals -- Absorption and adsorption.